MODIFICATION OF AN AUTO-INDUCIBLE VECTOR FOR RECOMBINANT PROTEIN EXPRESSION ENHANCEMENT IN ESCHERICHIA COLI - Mulyanti, Dina
Recombinant therapeutic proteins have been widely produced and consumed. An auto-inducible expression vector has become an optional for the safety and effectiveness of the recombinant therapeutic protein production process, in order to replace inducer interference, which is uneconomic and could be harmful. In this research, an auto-inducible expression vector in the form of plasmid, pCAD2_sod, which was under dps (RpoS-dependent gene) promoter control, was modified to provide subunit sigma factor S (RpoS) at earlier growth phase, hence accumulates more target protein. pCAD2_sod had been constructed to automatically induce the expression of recombinant superoxide dismutase (SOD) from Staphylococcus equorum (rMnSODSeq) in the stationary growth phase of Escherichia coli. A synthetic RpoS coding region under rpoD promoter control (prpoD_rpoS) was inserted into pCAD2_sod and generated pCAD2 + _sod. This study aimed to obtain pCAD2 + _sod and analyze the effect of the addition of prpoD_rpoS fragment toward rMnSODSeq protein yield and its mRNA expression in the exponential and stationary phase of recombinant E. coli TOP10. The rMnSODSeq (24.3 kDa) produced from pCAD2 + _sod was higher (~1.5 fold) at 37 °C and more intense at 43 °C compared to that produced from pCAD2_sod. The rMnSODSeq protein was observed to be shifted expressed earlier to the exponential phase (after 1 h of incubation), as shown in the SDS-PAGE electrophoregram, and still retained its dismutase activity in zymography assay. The mRNA level of rMnSODSeq from pCAD2 + _sod in all growth phases gave a consistently lower Cq values compared to the one carried pCAD2_sod, which was also statistically significant (P<0.05) towards non recombinant control in the mid and late- exponential phase. Relative quantification values of the mRNA towads rho reference gene are also higher. Despite the insertion of prpoD_rpoS fragment to the pCAD2 + _sod vector was able to enhance the rMnSODSeq yield from E. coli TOP10 host cell that brought the vector, a direct role of RpoS towards rMnSODSeq expression enhancement needs to be confirmed further, since its mRNA level upon all samples was inconsistent. This research concludes that prpoD_rpoS fragment insertion shifts and increases the rMnSODSeq production from stationary to exponential phase, either in the mRNA or protein level. The pCAD2 + _sod plasmid is potential for further recombinant protein productions.